Formação, trabalho e identidade: expectativas pessoais e profissionais de futuros médicos - Souza, Maria Elizabet Lautert de (2012)
The topic of this research is the relationship between training, work and identity. The study aims to explore medical students' expectations regarding their personal and professional future. Its main objective was to investigate how those students are affected by social and educational practices during training; what cultural influences shape their choices; how training in medicine contributes to the development of their professional identity; what changes characterize the initial expectations and the completion of the degree. The assumptions framing the investigation were: a) from the students' perspectives, training in medicine still revolves more around technical development rather than around a humanistic view; b) at the beginning of their training, students' expectations about the work to be carried out in the future do not match possible scenarios and, as the training progresses, those expectations become closer to reality; c) the expectations one has about work and about oneself are directly related to the culture and to the values projected by the context towards professional choices and practices. The subjects of this study are medical students at the completion of their degree, during the internship, and about to enter the professional market. The survey is bibliographic, documentary and qualitative and it takes up the form of a case study looking at data during the course. The empirical research methodology was based on the observation of curricular activities carried out by members of the internship, as well as on interviews about life oral histories. The choice of method aims to encompass the dimension of the subject in relation to the larger social dimension in order to allow the development of free narratives. Questions were asked about life history, training, expectations, social and professional insertion, achievements and projects, as well as the reasons guiding the choice of the medical career. The analysis of the narrative was guided by the Frankfurt School approach to Critical Theory and it sought to unpack the influence held by training and work upon the development of the subject's professional identity. The study derives from individuals' sociohistoric conception and their constitution as subjects whose development is subjected to the logic of capital, in which their subjectivities and identity constructions respond to a conception of life and work tied to that logic. The results highlight that: according to the students' views, training is still more technical than humanist; their understanding at the time of graduation is that training is an ongoing process; their expectations are predominantly geared for success in the initial period of residence as a way to develop better qualification for the professional market rather than for personal life projects; their professional identities are still undergoing transformation including feelings of fear and pride, cultural influences are noticeable in their choices and training and so are the influences of models including friends, family and teachers who end up having an effect on the development of values and professional identity. As for training, we suggest new research about students in training and about their trainers and their pedagogical work in medicine